“Cuantificación de biomasa aerea en plantaciones forestales de shaina colubrina glandulosa perk (ramnaceae). En región San Martín-Perú” - Del Castillo Ugarte, Roberto Carlos (2003)
The objective of the study was to estímate the quantification of air biomass in forest plantations 6,5 years old, multietáneos, of the species Shaina Colubrina glandulosa Perk, located in the sector Lagoon Venice", District of the Band of Shilcayo, County and Region of San Martin - Peru. Coordinated Geographical: 06º 32' South Latitude and 76º22' Longitude West, half altitude of 350 msnm. The biomass was determined by means of a combination of the crop methods and alométrico. In the forest three parcels of inventory silvícola settled down, 38 trees were selected far a destructive sampling, distributed in three phases of growth: Latizal under, high Latizal and Fusta!. Each tree was turned, trozado and separated in the component bark and wood of the shaft, foliage and branches of the glass, being obtained its dry pesos. With 23 trees of the forest, equations alométricas were adjusted that estimated the dry weight of the components and total of the trees, using how variable predictoras the diameter to the height of the chest and the height fusta! of them. The rest of the trees muestreados allowed to validate those equations. The pattern of the described equations was ANO= to X. The equations of biomass of the shaft, it surrounds and total tree was applied on charts volumétricas of the forest in study, the total biomass accumulated by tree being determined, components and far the forest in general far hectare. The values total dasométricos of the forest were: 2 157 arbores/ha; basal areas of 8,20 m2 /ha; dominant heights of 10,5 m and gross volumes of 35,5 m3/ha. The accumulated biomass air total is of 109,9 t/ha; of which 82,8% corresponds to shafts (6,6% bark and 76,2% wood) and 17,2% to glasses (5, 1 % foliage and 12, 1 % branches). The total biomass in the phases of growth of the forest: Latizal Under, High Latizal, and Fusta! contributes 12, 1 %, 51.3% and 36,6% respectively.